Comparative Study on Weighting Customer Requirements using Fuzzy Analysis Hierarchy Process with Extent Analysis and Analytic Hierarchy Process - Mastura, M.T.; Sapuan, S.M.; Mansor, M.R.; Nuraini, A.A. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Weighting customer requirement is not an easy task to undertake since it involves subjective human perception and judgement. In this study, both Analytic Hierarchy Process (AHP) and Fuzzy AHP with extent analysis (FAHP) methods were applied to determine and to compare the differences on the weight of customer requirements. Customer requirements for automotive anti-roll bar (ARB) were taken as a case study from related literature. The results from both methods showed slight differences in weighting customer requirements with an average of differences is 0.73%. Thus, the FAHP method could be applied in decision-making to find the weight of attributes whilst the AHP could also be applied in decision-making to deal with vague and imprecise information.